Spatiotemporal Distribution and Population Structure of Monokalliapseudes schubarti (Tanaidacea: Kalliapseudidae) in an Estuary in Southern Brazil - Felipe Freitas-Júnior; Martin Lindsey Christoffersen; Joafrâncio Pereira de Araújo; Joaquim Olinto Branco (The Scientific World Journal)
Monokalliapseudes schubarti is an endemic tanaidacean microcrustacean from southeastern Brazil to Uruguay inhabiting low energy estuaries. Saco da Fazenda is located in the estuary of the Itajaí-Açú River, state of Santa Catarina, Brazil. It is exposed to strong anthropic impact and receives intensive flows of domestic wastewater, solid residues, and drainage activities. Specimens of M. schubarti were collected monthly, in the intertidal and subtidal regions of Saco da Fazenda, in four stations defined as a function of the physiography of the environment during the period of July 2003 to June 2004. Fecundity values were high, with continuous reproductive activity during the whole period of study. The greatest population densities were observed in the intertidal region, where they are nevertheless intensely consumed by birds, swimming crabs, and fish. This species represents a fundamental link in the food chain of Saco da Fazenda, transferring energy from the detritus level to higher trophic levels. Habitat disturbance and high organic matter may represent factors controlling the distribution of populations of M. schubarti. For this reason, the species may be used to monitor anthropic effects in estuarine areas.